2007
DOI: 10.1080/00379271.2007.10697495
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of emergence, calling behaviour and oviposition period of the maize stem borer,Busseola fusca(Fuller) (Lepidoptera: Noctuidae)

Abstract: Abstract. Sexual behaviour in most of the noctuid Lepidoptera follows a diel periodicity and is limited to a precise period of either the day or the night. The periodicity and the maturation periods are specifi c as well as the onset of oviposition behaviour. The knowledge of these traits of biology is an essential prerequisite for all the studies in chemical ecology. The periodicity of adult emergence, calling behaviour and oviposition of Busseola fusca (Fuller) was studied under laboratory conditions. Most m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…In all, there were ten replicates. To obtain sufficient mated females, the method developed by Calatayud et al (2007) was followed. One-day-old females were placed into glass jars with the onset of the evening and one day old males were introduced one hour later.…”
Section: Time Of Ovipositionmentioning
confidence: 99%
“…In all, there were ten replicates. To obtain sufficient mated females, the method developed by Calatayud et al (2007) was followed. One-day-old females were placed into glass jars with the onset of the evening and one day old males were introduced one hour later.…”
Section: Time Of Ovipositionmentioning
confidence: 99%
“…A cotton pad moistened with water maintained the relative humidity in the plastic box at [80%. Calatayud et al (2007) showed that no calling activities occurred during the photophase. Thus to allow carrying out of the experiments during day-time, the pupae were kept in a L12:D12 reversed photoperiod with the scotophase lasting from 07:00 to 19:00.…”
Section: Methodsmentioning
confidence: 98%
“…Calling was defined as 50% of full extension of the ovipositor. To determine the onset of calling, virgin females were placed in a mosquito-net cage (40 9 40 9 63 cm) the night succeeding emergence because they have a one day pre-oviposition period (Shorey et al 1968;Calatayud et al 2007). …”
Section: Determination Of the Onset Of Calling Timementioning
confidence: 99%
“…Adults were collected daily, and males were housed in groups of ten in rectangular crystal polystyrene boxes, while females were placed in individual containers for testing at 2-3 days old. All materials were held at 25°C, 85± 10% rh, under a 12:12 h light/dark reversed photoperiod, and the experiments were carried out during the mating period, which starts in the fifth hour of the scotophase under these conditions (Calatayud et al 2007). …”
Section: Methodsmentioning
confidence: 99%